Development and validation of the metacognitive processes during Performances Questionnaire. (March 2019) - Love, Steven; Kannis-Dymand, Lee; Lovell, Geoff P.
Abstract: Objectives: This study aimed to develop and validate a sport-specific self-report measure of metacognitive processes: The Metacognitive Processes during Performance Questionnaire (MPPQ). Design: Three sub studies were used to: a) test the internal validity of the MPPQ in an online athlete sample; b) retest the internal validity of the MPPQ in a triathlete field sample; and c) test the external validity of the MPPQ in an online athlete sample. Method: Firstly, principal components analysis was used to identify an adequate factor structure; secondly, confirmatory factor analysis was used to retest the factor structure; and thirdly, correlations and regressions were used to test concurrent validity. Reliability analyses were also used in each phase to test internal consistency. Results: principal components analysis and reliability tests indicated that a three-factor solution pertaining to: cognitive coordination, cognitive evaluation, and thought control was adequately reliable. Secondly, confirmatory factor analysis on a field sample supported this factor structure and also demonstrated adequate internal consistency. Finally, bivariate correlations and multiple regressions indicated that convergent, discriminate and predictive validity were present, with existing generalised metacognitive measures (the Metacognitions Questionnaire 30, the Metacognitive Awareness Inventory, the Five Facet Mindfulness Questionnaire – Short Form, the Psychological Skills Inventory for Sports, and the Coping Flexibility Scale). Conclusion: Overall, the results have demonstrated that the MPPQ is a sound measure of metacognitive processes that athletes might experience during competitions and presented several considerations for future research. Highlights: 3 factors found: cognitive coordination, cognitive evaluation, and thought control. Good model fit found using confirmatory factor analysis. Adequate internal consistency across three samples. Significantly associated with existing metacognitive measures. Significantly predicted concentration and coping flexibility.